Metabolic regulation of endothelial senescence - Le, Nhat-Tu (Frontiers in Cardiovascular Medicine, 2023)
Endothelial cell (EC) senescence is increasingly recognized as a significant contributor to the development of vascular dysfunction and age-related disorders and diseases, including cancer and cardiovascular diseases (CVD). The regulation of cellular senescence is known to be influenced by cellular metabolism. While extensive research has been conducted on the metabolic regulation of senescence in other cells such as cancer cells and fibroblasts, our understanding of the metabolic regulation of EC senescence remains limited. The specific metabolic changes that drive EC senescence are yet to be fully elucidated. The objective of this review is to provide an overview of the intricate interplay between cellular metabolism and senescence, with a particular emphasis on recent advancements in understanding the metabolic changes preceding cellular senescence. I will summarize the current knowledge on the metabolic regulation of EC senescence, aiming to offer insights into the underlying mechanisms and future research directions.